Pendampingan Wirausaha Berbasis Ekonomi Manajerial untuk Peningkatan Daya Saing UMKM di Cikarang Barat - Etty Zuliawati Zed; Melani Putri; Vanessa Dwie Meimita; Ulan Ulan; Ayu Amanda Damanik (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to improve the competitiveness of MSMEs through mentoring entrepreneurs based on managerial economics. Many MSMEs have not optimally implemented managerial principles, such as financial planning, market analysis, and decision-making strategies. The managerial economic approach is used to help MSMEs understand consumer behavior, cost efficiency, and effective resource management. The implementation methods for this activity include field observation, training, interactive discussions, and direct mentoring for MSMEs in the target area. The results of this activity show an increase in participants' understanding of business management, such as the implementation of more measurable strategies to face market competition. Thus, mentoring based on managerial economics has proven effective in strengthening the foundations of entrepreneurship and increasing the competitiveness of MSMEs in a sustainable manner.